Case 3555: Chilodontidae Macalister, 1876 (Ciliophora), Chilodontinae Eigenmann, 1910 (Pisces, Characiformes), and Chilodontinae Wenz, 1938 (Mollusca, Gastropoda): proposed resolution of homonymy between family-group names - Herbert, D G; Bouchet, P (Bulletin of Zoological Nomenclature, 2011)
The purpose of this application, under Articles 29 and 55 of the Code, is to remove the homonymy between the family-group names Chilodontidae Macalister, 1876 (type genus Chilodon Ehrenberg, 1834 [Ciliophora]), Chilodontinae, an emendation of Chilodinae Eigenmann, 1910 (type genus Chilodus Müller & Troschel, 1844 [Pisces]), and Chilodontinae Wenz, 1938 (type genus Chilodonta Étallon, 1859 [Gastropoda]). It is proposed to place the unused name Chilodontidae Macalister, 1876 on the Official Index; to place the name Chilodontinae Eigenmann, 1910, as emended by Fowler (1950), on the Official List; and that the stem of the generic name Chilodonta Étallon, 1859 be deemed to be Chilodonta-, such that the name Chilodontinae Wenz, 1938 is emended to Chilodontainae Wenz, 1938.
Keywords: Nomenclature; taxonomy; Ciliophora; Pisces; Characiformes; Vetigastropoda; SEGUENZIOIDEA; CHILODIDAE; CHILODONTIDAE; CHILODONELLIDAE; homonymy; ciliates; fish; gastropods